A comparison of the effects of inhaled furosemide and ethacrynic acid on sodium-metabisulfite-induced bronchoconstriction in subjects with asthma. - Pye, S; Pavord, I; Wilding, P; Bennett, J; Knox, A; Tattersfield, A (1995)
Inhaled furosemide prevents bronchoconstriction induced by a number of challenges in asthma. One approach to determine the mechanism underlying this protection has been to examine the effects of diuretics with different or overlapping pharmacologic effects. We have compared the effects of furosemide on sodium metabisulfite-induced bronchoconstriction with those of equivalent diuretic doses of ethacrynic acid, a loop diuretic that, unlike furosemide, does not interact directly with the membrane Na/K/Cl cotransporter protein or inhibit carbonic anhydrase. Eight subjects with mild asthma were studied on five occasions, receiving nebulized furosemide (20 and 40 mg), ethacrynic acid (25 and 50 mg), or placebo (normal saline) in random order and double-blind 10 min before a cumulative dose challenge with inhaled sodium metabisulfite. After placebo the geometric mean sodium metabisulfite PD20 was 7.9 mumol. Furosemide 20 mg and 40 mg increased the PD20 by a mean 1.1 (95% confidence interval, -0.2-2.4; p > 0.05) and 1.6 (0.4-2.9; p < 0.02) doubling doses to 17.1 and 24.7 mumol, respectively. After inhaled ethacrynic acid 25 mg and 50 mg, the geometric mean PD20 was increased by 0.9 (-0.4-2.2; p > 0.05) and 1.5 (0.2-2.8; p < 0.05) doubling doses to 14.5 and 22.4 mumol, respectively. Thus, equivalent diuretic doses of furosemide and ethacrynic acid have a similar inhibitory effect on sodium metabisulfite-induced bronchoconstriction in asthma. This suggests that interaction with the Na/K/Cl cotransporter protein, or carbonic anhydrase inhibition, is not relevant to the effects of furosemide in asthma.